Proyecto de factibilidad para la expansión geográfica a nivel nacional mediante alianzas estratégicas con instituciones financieras para la empresa servipagos. - Puente Calle, Martín Alejandro (2013)
Having determined that there was a need Servipagos operational expansion into new markets in rural areas, but they had the proper market research, technical, economic and financial, it is possible to solve an important need two sectors present in the Coca and Biblián, so that the purpose or proposal of this research is to answer the questions posed, trying to find solutions to identify and characterize the role of a new business to be implemented in a technical. Determining the scope of the investigation to the current situation of the development of a business plan, in which is considered potential users of a service of entertainment, they constituted the primary analysis unit.